2017
DOI: 10.1177/0961203317694258
|View full text |Cite
|
Sign up to set email alerts
|

Pincer nail in a lupus patient

Abstract: Pincer nail is a transverse overcurvature of the nail plate that may appear in association with a variable number of diseases. We present a case report of a 28-year-old woman with pincer nail deformity associated with systemic lupus erythematosus. A renal biopsy confirmed class V lupus nephritis and treatment had included systemic steroids and cyclophosphamide. After 6 months there was a marked improvement of nail deformities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 7 publications
0
5
0
3
Order By: Relevance
“…In another case, reported by Twigg et al [14], the patient developed pincer nail deformity 12 years after the diagnosis of SLE, and there were no other cutaneous manifestations of SLE. Recently Azevedo et al reported an SLE patient with class V lupus nephritis who had classic cutaneous, musculoskeletal and psychiatric features of SLE with pincer nail deformity [15]. Interestingly, our patient did not develop any specific cutaneous manifestations of SLE or any signs of hepatitis, despite the high Dermatology Review/Przegląd Dermatologiczny 2017/3 występowania objawu Raynauda i owrzodzeń błony śluzowej jamy ustnej u pacjentów z SLE ze zmianami paznokciowymi [19].…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…In another case, reported by Twigg et al [14], the patient developed pincer nail deformity 12 years after the diagnosis of SLE, and there were no other cutaneous manifestations of SLE. Recently Azevedo et al reported an SLE patient with class V lupus nephritis who had classic cutaneous, musculoskeletal and psychiatric features of SLE with pincer nail deformity [15]. Interestingly, our patient did not develop any specific cutaneous manifestations of SLE or any signs of hepatitis, despite the high Dermatology Review/Przegląd Dermatologiczny 2017/3 występowania objawu Raynauda i owrzodzeń błony śluzowej jamy ustnej u pacjentów z SLE ze zmianami paznokciowymi [19].…”
Section: Discussionmentioning
confidence: 61%
“…Ostatnio Azevedo i wsp. przedstawili pacjenta z SLE oraz nefropatią toczniową klasy V, u którego stwierdzono klasyczne skórne, mięśniowo-szkieletowe i psychiczne zaburzenia typowe dla SLE, a także paznokcie pincetowate [15]. Co ciekawe, u naszej pacjentki nie wystąpiły żadne swoiste objawy skórne SLE ani objawy zapalenia wątroby pomimo bardzo wysokiego miana przeciwciał ANA, anty-dsDNA oraz dodatnich przeciwciał anty-AMA-M2 i przeciwciał przeciwko nukleosomom.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…100,106 Many other nail changes have been reported in systemic lupus erythematosus, including Beau's lines, onychomadesis, pitting, chronic paronychia, subungual hyperkeratosis, leukonychia, increased transverse or longitudinal nail curvature, pincer nails, and clubbing. 20,105,107 Onycholysis seems to be the most common finding (25%-40%). 103,104 Red lunula can be the presenting sign of systemic lupus erythematosus 73 and has been found in up to 20% of patients with lupus.…”
Section: Yellow Nail Syndromementioning
confidence: 99%